Komponen Biaya Promosi dari Marketing Mix Terhadap Volume Penjualan Jasa Tur dan Travel di Medan - Elserra Siemin Ciamas (Journal of Trends Economics and Accounting Research, 2023)
The development of the tourism industry in Medan has increased since 2018. This can be seen from the increasing number of hotels, culinary delights and various other entertainment facilities, which of course has also increased the number of local and foreign tourists. Therefore, Tour and Travel services in Medan can be a business opportunity. To be able to run a Tour and Travel Services business, of course, promotional efforts are needed. This study processes Promotional Cost data as a component of the Marketing Mix with a case study at PT. Cheers Universe Travel. PT. Ceria Wisata Semesta is a company that sells tickets, provides tour, travel, bus & hotel services. The purpose of this study aims to determine the effect of the amount of promotion costs as a component of the marketing mix on the sales volume of PT. Cheerful Travel Universe Cemara Asri, Medan. The method used by researchers is associative quantitative. The analysis of measuring instruments in this study used tests of normality, linearity, correlation coefficients, coefficients of determination, simple linear regression and hypothesis testing. In this study it was found that promotion costs had a strong (positive) correlation with the sales volume of PT. Ceria Wisata Semesta with a value of rxy = 0.701. The coefficient of determination also shows that promotion costs have a relationship of 49.14% to sales volume, while the remaining 50.86% is influenced by other variables not examined. Simple Linear Regression Model Y = 52,294,685.141 + 48.674X. Constants of 52,294,685.141; meaning that if the Promotion Cost is 0, then the Sales Volume has a positive value of 52,294,685.141